Predictive Value of Obstetrical Doppler Parameters to Predict Oxidative Stress and Cord Blood PH in Newborn Infants - Korkmaz, Vakkas; Tosun, Alptekin; Özkaya, Enis; Menekşe Beşer, Dilek; Küçüközkan, Tuncay; Kara, Fadıl (Gynecology Obstetrics & Reproductive Medicine, 2014)
OBJECTIVE: We sought to determine the clinical value of obstetrical Doppler performed at early stages of active labor in predicting oxidative stress and cord blood pH in neonates. STUDY DESIGN: A total of 54 pregnant women with oligohydramnios who were in active labor were enrolled for the study. Active labor was confirmed for each woman according to uterine contraction frequency, cervical dilatation and effacement. Subjects with amniotic fluid index (AFI) lower than 80 mm were included in the study. Doppler assessment included uterine artery (UtA), umbilical artery (UmA) and middle cerebral artery (MCA) measurements. Umbilical cord lengths were measured after delivery. Cord blood gamma glutamyl transferase (GGT) levels and umbilical arterial blood pH were analyzed. RESULTS: Umbilical artery PI significantly predicted cord blood GGT levels >101 ıu/L (area under curve=0.690, P=0.018). Umbilical artery PI significantly predicted cord blood pH<7.21 (area under curve (AUC) =0.870, P=0.015). None of the MCA Doppler parameters were significantly correlated with cord blood pH or cord blood GGT (P>0.05). Also, MCA Doppler studies could not significantly predict cord blood pH<7.21 OR GGT>101(P>0.05). CONCLUSION: This data led us to conclude that UmA Doppler parameters at early periods of active labor in high-risk population may be predictive for newborn well-being.